Analysis The Effectiveness of State Civil Apparatus (ASN) Employee Performance in Public Services at The Personnel and Human Resource Development Agency of Murung Raya Regency - Serli Idiarti (Politeia : Journal of Public Administration and Political Science and International Relations, 2026)
Public service delivery at the Personnel and Human Resource Development Agency (BKPSDM) of Murung Raya Regency faces several operational challenges, including delays in service processes, inconsistencies in service accuracy, and variations in employee responsiveness as reflected in community complaints. This study aims to: (1) analyze the effectiveness of State Civil Apparatus (ASN) employee performance in public service delivery at BKPSDM Murung Raya Regency; and (2) identify the factors that hinder its effectiveness. This study employed a qualitative descriptive approach. Data were collected through semi-structured interviews with seven informants, consisting of 2 community members and 5 BKPSDM employees directly involved in service delivery. Data analysis was conducted using thematic analysis, including data reduction, coding, categorization, and interpretation to identify patterns in employee performance. The findings indicate that employee performance varies across several dimensions, including work planning, timeliness, service quality, responsiveness, and independence. Participants reported that although employees generally perform their duties in accordance with established procedures, inconsistencies remain in practice. Service processes are sometimes perceived as slow, administrative inaccuracies still occur, and responsiveness to community needs is not always optimal. In addition, time management and technical competence were identified as key factors influencing performance outcomes. These findings suggest that the effectiveness of ASN employee performance at BKPSDM Murung Raya Regency remains context-dependent and influenced by both individual capabilities and operational conditions. Improving procedural consistency, strengthening employee competence, and enhancing responsiveness are necessary to support more reliable and efficient public service delivery.